2011
DOI: 10.1007/s00348-011-1191-2
|View full text |Cite
|
Sign up to set email alerts
|

Flow field investigation in rotating rib-roughened channel by means of particle image velocimetry

Abstract: The turbulent velocity field over the ribroughened wall of an orthogonally rotating channel is investigated by means of two-dimensional particle image velocimetry (PIV). The flow direction is outward, with a bulk Reynolds number of 1.5 9 10 4 and a rotation number ranging from 0.3 to 0.38. The measurements are obtained along the wall-normal/streamwise plane at mid-span. The PIV system rotates with the channel, allowing to measure directly the relative flow velocity with high spatial resolution. Coriolis forces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 42 publications
5
49
1
1
Order By: Relevance
“…In the current work, numerical results by a hybrid k-ω RANS/LES model and the originating RANS k-ω model are compared with the experimental results by Coletti and Arts [6] and Coletti et al [7]. Coletti et al [7] observed that the Coriolis force affects the dynamics of both large and small scales, leading to complicated flow patterns with recirculation zones and secondary vortex motions.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…In the current work, numerical results by a hybrid k-ω RANS/LES model and the originating RANS k-ω model are compared with the experimental results by Coletti and Arts [6] and Coletti et al [7]. Coletti et al [7] observed that the Coriolis force affects the dynamics of both large and small scales, leading to complicated flow patterns with recirculation zones and secondary vortex motions.…”
Section: Introductionmentioning
confidence: 95%
“…The objective was fundamental study of the effect of the Coriolis force on turbulence enhancement or damping in a nominally 2D channel. The first, and probably still the only, PIV measurements of flow in a ribbed rotating duct, relevant for internal cooling channels of gas turbine blades, with the equipment rotating together with the duct, were realised by Coletti and Arts [6] and Coletti et al [7]. The cross-section of the duct is approximately square.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational modelling has played a very important role in identifying the underlying physics of cooling flows. Experiments have mostly measured the heat transfer coefficients without much regard to the underlying hydrodynamic mechanisms for a number of reasons, chief among them being the singular importance of heat transfer coefficients to the design process and the difficulty of making velocity measurements particularly in a rotating geometry, which is a challenge even to this day [2]. A vast number of numerical investigations have been performed to investigate the ability of numerical models, in particular turbulence models, to predict the heat transfer.…”
Section: Introductionmentioning
confidence: 99%